Tipping the spindle into the right position - Akhmanova, Anna (J Cell Biol, 2016)
The position of the mitotic spindle determines the cleavage plane in animal cells, but what controls spindle positioning? Kern et al. (2016. J. Cell Biol. http://dx.doi.org/10.1083/jcb.201510117) demonstrate that the microtubule plus end–associated SKAP/Astrin complex participates in this process, possibly by affecting dynein-dependent pulling forces exerted on the tips of astral microtubules.